Przekroczyć granicę: monstrum Frankensteina z powieści Mary Wollstonecraft Shelley = To cross the border: Frankenstein monster from the novel by Mary Wollstonecraft Shelley - Gemra, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The novel titled "Frankenstein" (published in 1818) written by Mary Wollstonecraft Shelley is one of the earliest and the most important piece of writing where the problem of the human - nonhuman appears. It is the problem of the being whose existence raises doubts of ethical and ontological origin. The reason for this is that this kind of creature is the source of existence of many different entities - not only of the human kind. While reading the novel by Shelley the questions about the limits of knowledge, life and death are posed, however, the most important thing here is that it calls for the definition of what it means to be human, for the definition of the word "humanity".
Keywords: człowiek; nie-człowiek; istota człowieka; transgeniczność; Frankenstein; monstrum; human being; non-human; the essence of human; transgenity; monster